Pengembangan Media Komik Berbasis Karakter - Fitria, Yuki Febriana Dwi; Mawartiningsih, Lilik (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2018)
This research is a development research that aims to produce character-based comics on the material excretion system for students of SMP / mt class8 quality.thus this comic can be used as a teacher reference in biology learning and can be used by learners as an additional source of learning.This development research uses the ADDIE model (Analysis, Desain, Development, Implementation, Evaluation). Assessment instruments used to assess the quality of character-based comics,namely in the form of a questionnaire covering several aspects, namely the truth and the extent of the concept, linguistic, character integration, appearance and implementation of learning.the quality of the comics was assessed by 2 media experts, 2 material experts, 5 pree reviewers, and 17 8th grade students SMP Ma’arif NU Asy-syafi’iyah Lohgung . in a limited trial.this data quality obtained in qualitative form then processed into quantitative data.Quantitative data are analyzed in every aspect of the assessment.the final score obtained is converted to qualitative level of product quality by guidance according to the criterion of idea rating category.thus the results of this development research indicate that the character-based comics on the material excretion system in humans for students of SMP / mts grade 8 memenyuhui kreteria quality and worthy of use as a biological teaching materials.